2021
DOI: 10.1080/23311975.2021.1880679
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rural Chinese consumers’ behavior: A stimulus–organism–response (S-O-R) perspective on Huawei’s brand loyalty in China

Abstract: This study examined the effect of familiarity with the Huawei smartphone brand as a mediator between brand involvement and brand loyalty in China and explored behavioral and attitudinal loyalty as two major components of brand loyalty. An exploratory mixed-methods design grounded in the stimulus-organismresponse (S-OR) framework entailed two rounds interviews to build a hypothetical framework, following which 403 Chinese smartphone users were surveyed to test the hypotheses. The results of structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
0
15
0
5
Order By: Relevance
“…According to Yu et al ( 2021 ), the effect of understanding the Huawei smartphone brand as an intermediary between brand involvement and brand loyalty in China and analyzed behavioral and attitudinal loyalty as two major elements of brand loyalty. An exploratory mixed-methods design leveled in the stimulus-organism-response (S-O-R) framework entailed two interviews to construct a theoretical framework.…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%
“…According to Yu et al ( 2021 ), the effect of understanding the Huawei smartphone brand as an intermediary between brand involvement and brand loyalty in China and analyzed behavioral and attitudinal loyalty as two major elements of brand loyalty. An exploratory mixed-methods design leveled in the stimulus-organism-response (S-O-R) framework entailed two interviews to construct a theoretical framework.…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%
“…Mehrabian and Russell (1974) indicated that this framework refers to the fact that environmental stimulus affects individuals' cognitive and affective responses, which are mediated by the organism [12]. Previous studies by Chopdar and Balakrishnan (2020) and Yu, Klongthong, Thavorn, and Ngamkroeckjoti (2021) have applied the SOR model to many areas of consumer behaviour, including mobile commerce and brand loyalty [13,14]. The present study draws on this model to structure its examination of IB in a live-streaming environment.…”
Section: Sormentioning
confidence: 99%
“…In order to predict the effects of social marketing activities such as interactivity, informativeness, word-of-mouth (WOM), personalization, and trends on online consumer commitment, trust, satisfaction, and repurchase intention, researchers have extensively employed organism-stimulus response theory (Ho et al, 2022;Malarvizhi et al, 2022;Sohaib et al, 2022;Svotwa et al, 2020;Yu et al, 2021). Several studies based on the theory of SOR reveal that social media platforms and social brand management have a positive impact on the intention to buy online market products (Hajli, 2014;Hutter et al, 2013;Vo Minh et al, 2022).…”
Section: Stimulus-organism-response (S-o-r)mentioning
confidence: 99%